Aspek Teologi Menurut KH. Hasyim Asyari: Antara Kepercayaan dan Ketetapan - Yunita Kurniati (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2022)
This scientific work aims to find out about the thoughts of KH. Hayim Asyari in the field of actual theology, because among the people, his thoughts have experienced a lot of conflict, both among Islamic scholars and thinkers, and also the general public. For this reason, the question in this paper is about the theological thoughts of KH. Hasyim Asyari himself. The methodology used in this research is library research, namely research conducted by collecting library data as the data used in this paper. Then regarding the data analysis techniques used in this study are descriptive data analysis techniques and analysis. From this paper it is found that the theological thought of KH. Hasyim Asyari contains three aspects, namely about divinity, the Koran, and qadha and qadar. Regarding his thoughts on divinity KH. Hasyim Asyari said that God is One, and has no equal in this world. As for the Koran KH. Hasyim Asyari said that the Koran is the word of Allah SWT, which was revealed in the world through the angel Jibril to the Prophet SAW, so the Koran is qadim. Meanwhile regarding qadha and qadar, KH. Hasyim Asyari said that this is very related to human actions, where human actions are very related to God's actions. Meanwhile regarding the suitability of KH. Hasyim Asyari with the Indonesian context is very appropriate, even his thoughts still have a big influence on Indonesian society from various groups.